Students as Community-Engaged Researchers in Responding to Crises: Insights From the Embedded Thesis Model - Shasta Grant; Adhika Ezra (Journal of Community Engagement and Scholarship)
The Community-Campus Responses to Crisis project, led by Community Campus Engage Canada and the University of Regina, explores how postsecondary institutions can best support community initiatives that address social impacts of climate change. The project aims to strengthen universities’ capacity to support community initiatives and build a pan-national knowledge-sharing network that centralizes effective crisis response strategies. The project involves case studies at Canadian institutions, two of which—the University of Regina and Acadia University—focused on community engagement efforts with homelessness-related organizations. These two case studies used an embedded thesis model that allows graduate students to lead the community engagement process, determine the direction of the research, and integrate the study into their thesis. This reflection explores the experiences of two master’s students (Adhika, University of Regina, and Shasta, Acadia University) who participated in the embedded thesis model.